Baal kaj Anat - Broadribb, Donald (1966)
discussion and translation (in Esperanto) of Gordon, UT, texts 137, 68 = III AB, В, III AB, A; UT, text ‛nt; UT, text 51 = II AB; UT texts 67, 62, 49 = I*AB, I AB; UT, text 76 = IV AB.